Characteristics of mantle branch structure in western Shandong and its roles in minerogenesis and ore-controlling - 孙爱群 胡华斌 牛树银 毛景文 王宝德 李英平 王来明 (Chinese journal of geochemistry, 2006)
This work deals with the characteristics of mantle branch structure in western Shandong Province, China, with respect to the distribution characteristics and ages of the regional strata, the development of ring-like and radial faults, the development of gently inclined detachment-slip structures in the axial part, mantle-source magmatic activities, regional petrology, petrochemistry and isotope geology. The study indicated that the N-W sharply plunged ductile shear zone in the region of western Shandong cuts through the mantle rocks detached from the deep-seated North China mantle sub-plume, hence leading to unloading in response to depressurization and thereafter the formation of anatexis magma. The intense and complete magmatic evolution series not only manifests a variation trend of alkalinity of magma from high to low and its intrusive depth from deep to shallow, but also reflects that the wall-rock alteration shows a general evolution trend from strong to weak. The evolution of mantle structure played an important role in controlling endo-mineralogenesis, accompanied with the rise of the country rocks. As a result, typical mantle branch structures were formed as observed in western Shandong. At the top of the mantle branch structure was developed an obvious detachment-tilt fault block, and some endogenic ores, at the same time, were uplifted onto the shallow levels.